2010
DOI: 10.18388/abp.2010_2372
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alpha3beta1 and alphavbeta3 integrin glycosylation on interaction of melanoma cells with vitronectin.

Abstract: The metastatic transformation of melanocytes is associated with altered expression of adhesion molecules, including alpha(v)beta(3) and alpha(3)beta(1) integrins. Integrin alpha(v)beta(3) is a primary vitronectin (VN) receptor, while both integrin types take part in adhesion to VN when they are in complex with uPAR. Although their role in melanoma cell interaction with VN is of great interest, the influence of N-oligosaccharides attached to these glycoproteins is still unappreciated. The present study assesses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…Our group has investigated the glycosylation profiles of melanoma cells for over fifteen years. We have clearly demonstrated that the glycosylation profile of adhesion proteins (mainly integrins) depends on the stage of tumor development (Pocheć et al, 2003, Przybyło et al, 2007Pocheć et al, 2013) and the location of metastasis (Kremser et al, 2008;Janik et al, 2010). Here we searched for the reasons of a different behavior of UM and CM cells in the surface glycosylation.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has investigated the glycosylation profiles of melanoma cells for over fifteen years. We have clearly demonstrated that the glycosylation profile of adhesion proteins (mainly integrins) depends on the stage of tumor development (Pocheć et al, 2003, Przybyło et al, 2007Pocheć et al, 2013) and the location of metastasis (Kremser et al, 2008;Janik et al, 2010). Here we searched for the reasons of a different behavior of UM and CM cells in the surface glycosylation.…”
Section: Introductionmentioning
confidence: 99%
“…Our work demonstrated that β1,6-branched oligosaccharides on αvβ3 and α3β1 integrins are essential for the association of the uPAR with integrins in human melanoma cell lines WM9 and WM239, seen in the failure of co-precipitation of the two integrins with the uPAR in SW-treated cells. Adhesion of the two melanoma cells to VN was dependant on β1,6 branching of αvβ3 and α3β1 integrins in a cell-line-specific manner [76].…”
Section: Different Techniques Have Been Employed To Analyze α3β1mentioning
confidence: 92%
“…It has been demonstrated that the glycosylation profile of integrins depends on the stage of melanoma development [37,58,59,74] and the location of the metastasis [75,76] and that glycosylation is essential to the interaction between integrin and ECM proteins during adhesion and migration processes [58,75,76]. These studies have produced ample evidence for the presence of glycoforms associated with melanoma carcinogenesis on α3β1, α5β1, and αvβ3 integrins.…”
Section: Alterations Of Integrin Glycosylation In Melanoma Carcinogenmentioning
confidence: 99%
“…We demonstrated that not only gain or loss of adhesion molecule expression and increased level of β1,6-branched N-oligosaccharides, but also changes in the number of proteins being a substrate for GnT-V appear to be a consequence of disease progression from a tumourigenic to the metastatic phenotype. The involvement of these glycoproteins in adhesion and migration of cutaneous melanoma cells has been clearly demonstrated [60,62,63,[66][67][68][69][70][71]. In general, overexpression of β1,6-branched N-glycans on cell adhesion molecules contributed to the significant decrease in these cell adhesion level to extracellular matrix components, loss of contact inhibition as well as increased motility in vitro and enhanced metastasis in vivo.…”
Section: Glycosylation and Melanomamentioning
confidence: 97%